SYNTHESIS OF NiO–ZnO NANOPARTICLES BY PYROLYSIS OF Ni–ZIF–8 AND PHOTOCATALYTIC ACTIVITY UNDER SUNLIGHT - Thanh, Mai Thị; Châu, Bùi Thị Minh; Thành, Hồ Văn; Khiếu, Đinh Quang (Hue University Journal of Science: Natural Science, 2017)
This paper presents the study on the synthesis of NiO–ZnO semiconductor nanoparticles from Ni–ZIF–8. The Ni–ZIF–8 material prepared from 2–methyl imidazole and a solution containing Ni2+ and Zn2+ with an Ni2+/Zn2+ molar ratio of 8:2 has the crystallinity of ZIF–8 with the space. The p–n NiO–ZnO nanoparticles were prepared by the thermal treatment of Ni–ZIF–8 at 500 °C for 4 hours. The obtained semiconductors exhibit photocatalytic activity for the degradation of Remadazol Deep Black dye under sunlight with high efficiency.